(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Lichen planus characterized by its violaceous color most commonly seen on the flexor surfaces of the upper extremities, the genitalia and the mucous membranes. Psoriasis is a common, chronic, relapsing, inflammatory skin disorder with a strong genetic basis. Plaque type of psoriasis is the most common. Selenium is a component of the enzyme glutathione peroxidase, and is important in protection against damage by peroxides and free radicals. Objectives: To measure selenium level in Iraqi patients with lichen planus and in patients with psoriasis and its relation to the chronicity and the severity of both diseases. Methods: One hundred twenty patients were included in this study, 68 males and 52 females, with ages between 18-54 years. Full history and examination, including dermatological examination, were done for all patients. The patients were divided into three groups. The first group includes lichen planus patients, the second group includes psoriasis patients and the third group was a control group study. Serum selenium level was measured for all patients by spectrophotometer. Results:Serum selenium level was decreased in 20 (50%) patients of the first group, in 32 (80%) patients of the second group and 14 (35%) of the third group. The results were of high statistical significance when compared between groups 2 & 3 but it was insignificant when compared between groups 1 & 3. Selenium level was decreased in 12 of the first group who had the disease for two years and above while it was decreased in 18 of the second group who had psoriasis for two years and above, selenium level was decreased in patients with severe and diffuse variants of both lichen planus and psoriasis. Conclusion: Serum selenium level was decreased in both lichen planus and psoriasis but it was more significant in psoriasis and this decrease was related to both chronicity and severity. Keywords: Selenium, Lichen planus, Psoriasis, Chronicity, Severity.